Livelihood impacts of job-related illnesses among informal waste workers in Kathmandu Metropolitan City, Nepal - Ashish Khanal; Bhawna Bali (International Journal of Occupational Safety and Health)
Introduction: Informal Waste Workers (IWWs) face numerous occupational hazards, including exposure to toxic materials and a lack of safety measures, which can lead to various health issues. This study investigates the prevalence of job-related illnesses among IWWs in Kathmandu Metropolitan City (KMC) and identifies the most common types of illnesses experienced.